Estimated Ventricular Size, Asthma Severity, and Exacerbations: The Severe Asthma Research Program III Cohort - Ash, Samuel Y; Sanchez-Ferrero, Gonzalo Vegas; Schiebler, Mark L; Rahaghi, Farbod N; Rai, Ashish; Come, Carolyn E; Ross, James C; Colon, Alysha G; Cardet, Juan Carlos; Bleecker, Eugene R; Castro, Mario; Fahy, John V; et al. (Chest, 2020)
Relative enlargement of the pulmonary artery (PA) on chest CT imaging is associated with respiratory exacerbations in patients with COPD or cystic fibrosis. We sought to determine whether similar findings were present in patients with asthma and whether these findings were explained by differences in ventricular size. We measured the PA and aorta diameters in 233 individuals from the Severe Asthma Research Program III cohort. We also estimated right, left, and total epicardial cardiac ventricular volume indices (eERVVI, eELVVI, and eETVVI, respectively). Associations between the cardiac and PA measures (PA-to-aorta [PA/A] ratio, eERVVI-to-eELVVI [eRV/eLV] ratio, eERVVI, eELVVI, eETVVI) and clinical measures of asthma severity were assessed by Pearson correlation, and associations with asthma severity and exacerbation rate were evaluated by multivariable linear and zero-inflated negative binomial regression. Asthma severity was associated with smaller ventricular volumes. For example, those with severe asthma had 36.1 mL/m smaller eETVVI than healthy control subjects (P = .003) and 14.1 mL/m smaller eETVVI than those with mild/moderate disease (P = .011). Smaller ventricular volumes were also associated with a higher rate of asthma exacerbations, both retrospectively and prospectively. For example, those with an eETVVI less than the median had a 57% higher rate of exacerbations during follow-up than those with eETVVI greater than the median (P = .020). Neither PA/A nor eRV/eLV was associated with asthma severity or exacerbations. In patients with asthma, smaller cardiac ventricular size may be associated with more severe disease and a higher rate of asthma exacerbations. ClinicalTrials.gov; No.: NCT01761630; URL: www.clinicaltrials.gov.